Postpartum Body Composition in Women With Overweight: Associations With Diet During Pregnancy - Muhli, Ella; Vahlberg, Tero; Saros, Lotta; Houttu, Noora; Pellonperä, Outi; Tertti, Kristiina; Laitinen, Kirsi (Wiley, 2026)
Objective: Weight management during the first few years postpartum is considered important for the prevention of future metabolic disturbances. Body fat percentage measured using air displacement plethysmography is an accurate marker of body adiposity. In this secondary analysis of a randomized controlled trial, the aims were to identify distinctive body fat percentage trajectories up to 2 years postpartum in women with overweight and to investigate whether fish oil and/or probiotic supplements, diet, gestational diabetes, or gestational weight gain influenced the body composition.
Methods: Women with overweight or obesity (n = 439) were randomized to receive fish oil (1.9 g docosahexaenoic acid and 0.22 g eicosapentaenoic acid) and/or probiotics (Lacticaseibacillus rhamnosus HN001 and Bifidobacterium animalis ssp. lactis 420, 1010 CFU each) in a double-blind manner from early pregnancy until 6 months postpartum. Body composition (n = 329) was measured using air displacement plethysmography, at three, six, 12, and 24 months postpartum. Diet in early pregnancy was evaluated using nutrient intakes, dietary patterns, and the Index of Diet Quality (IDQ) questionnaire.
Results: Three postpartum body fat percentage trajectories were identified, but none displayed a sustained decrease in adiposity. A healthy dietary pattern (adjusted OR 5.8 [95% CI 2.5-13.5], p < 0.001) and high IDQ score (adjusted OR 2.5 [95% CI 1.1-5.5], p = 0.023) in early pregnancy increased the odds of a decreasing trend during the first postpartum year. The fish oil and/or probiotic intervention did not impact the body composition.
Conclusion: Good overall dietary quality during pregnancy may benefit the body composition of women with overweight or obesity at postpartum.
Trial registration: NCT01922791, ClinicalTrials.gov.
Keywords: body composition; diet; obesity; postpartum; pregnancy.